Eco-Friendly Concrete Technology Innovation for Sustainable Construction in Modern Cities - Sitorus, Henry Baginda Polianus (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The rapid urbanization across the globe has increased the demand for environmentally sustainable construction materials, particularly concrete, which alone contributes to over 8% of global carbon emissions due to cement production. Addressing this environmental concern, this study aims to explore eco-friendly concrete technologies that can support the development of sustainable and resilient urban infrastructure. Utilizing a systematic literature review (SLR) method, this qualitative research synthesizes findings from peer-reviewed sources and policy documents published between 2018 and 2025. The study focuses on evaluating technological, environmental, and economic dimensions of green concrete innovations including geopolymer concrete, self-healing concrete, recycled aggregate concrete, CarbonCure technology, and ultra-high-performance concrete (UHPC). Findings reveal that these technologies offer significant carbon reduction potential (up to 90%), enhance durability, support circular economies through waste reuse, and extend infrastructure lifespan. However, challenges such as high initial costs, lack of technical standardization, and policy gaps, especially in developing countries like Indonesia, hinder their widespread adoption. The study recommends multi-stakeholder collaboration, smart urban labs for field testing, financial incentives, and integration of life cycle assessment (LCA) frameworks in urban planning as strategic pathways for implementation. The paper concludes that eco-friendly concrete technologies hold substantial promise for sustainable construction in modern cities and align well with national and global environmental goals. Their integration is essential for reducing emissions, improving efficiency, and building climate-resilient urban ecosystems.